Peningkatan Mutu Keagamaan Anak Usia Sekolah Melalui Gerakan Maghrib Mengaji di Desa Palimanan Timur, Cirebon - Via Nurpajriah; Anton Sudrajat (Dimasejati: Jurnal Pengabdian Kepada Masyarakat, 2023)
To anticipate the negative impacts of the development of information and communication technology, school-age children must be properly educated and guided, and equipped with religious activities that can instill morals and spirituality in children through the maghrib recitation movement which invites school-age children to fill the time between maghrib and isya with recitation activities at the mosque or musholla. The purpose of the maghrib recitation movement is to increase the motivation and interest of school-age children in reciting Qur’an as well as to revive and prosper the mosque with religious activities that can improve the religious quality of school-age children through the Qur’an learning assistance program, PAI tutoring, and religious literacy. Data collection techniques using the method of observation, documentation, and interviews. While the data analysis uses the Miles and Huberman analysis method where qualitative data analysis is carried out interactively and continues continuously until complete with data reduction, data display, and conclusion. The results of the maghrib recitation movement have a positive impact on increasing the ability of school-age children to recite Qur’an, to understand PAI lessons, and to have a high interest in religious literacy so that they can improve the religious quality of school-age children as a provision for the future.